Устройства измерения температуры на основе пленочных термоэлектрических сенсоров - Kapitanov, N. V.; Kopyl, A. I.; Kosobutsky, S. I.; Razinkov, V. V.; Seredyuk, A. I. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Thin-film thermoelectric sensors based on narrow-gap semiconductor solid solutions were studied for the development of autonomous IR detectors and other instruments. Circuit diagrams and application methods for medicine, veterinary science, industry, and agricultural technology are presented. Techniques for analog and microprocessor implementations of the devices are proposed, providing verification, noise immunity, and data archiving capabilities.